Gender Affirming Surgery Experience and Exposure among Reconstructive Urologists. Issue 3 (7th May 2020) - Sukumar, Shyam; Pijush, Debduth B.; Brandes, Steven B.
Abstract: Introduction: There is a paucity of data on contemporary practice patterns regarding gender affirming surgery among reconstructive urologists. Methods: We surveyed members of GURS (Society of Genitourinary Reconstructive Surgeons), an international association of mostly academic urologists specializing in urological reconstruction. An 18-question leadership approved survey was emailed to every member of the society globally. Multivariable logistic regression models assessed factors influencing attitudes toward gender affirming surgery. Results: Of 304 members surveyed 80 (26%) completed the questionnaire. Of the respondents 89% had seen a transgender patient in their practice in the preceding year, with most (76%) seeing 10 or fewer transgender patients yearly. Of the respondents 50% stated that their organization wanted to develop a multidisciplinary gender affirming surgery program. Only 5% performed primary gender affirming surgery, and the most common procedures (43%) involved correction of complications of primary surgeries performed elsewhere. Of the respondents 66% were interested in pursuing additional gender affirming surgery training, and 75% thought that gender affirming surgery should be a discipline within GURS. Being in an organization that wanted to develop a multidisciplinary program predicted for desire to pursue additional gender affirming surgery training (OR 6.46, p=0.006) and the belief that gender affirming surgery should be a GURS subdiscipline (OR 4.42, p=0.032). Age 40 years or older predicted for belief that gender affirming surgery should not be covered by public insurance programs (OR 0.12, p=0.012). Conclusions: Most reconstructive urologists see a low volume of transgender patients and repair complications of primary gender affirming surgery performed elsewhere. Most respondents think that gender affirming surgery should be a discipline within GURS. Younger age and working for an organization interested in developing a multidisciplinary gender affirming surgery program influence positive attitudes toward gender affirming surgery.